Perbandingan Kemampuan Problem Solving Antara Siswa Yang Diajarkan Dengan Metode Ekspositori Dengan Metode Inquiry Pada Pelajran Matematika - Ahmad Taufik (Peneliti.net, 2021)
The purpose of this study was to determine the difference between the learning model that uses the expository learning model and the inquiry learning model of problem-solving. This study used a post-test-only control group design research design. The population in this study were MTs students. NW Putra Nurul Haramain class IX. Sampling using simple random sampling technique. Data collection techniques using tests and documentation. Data analysis using t-test by using the formula separated variance and poolend variance. The result of this study is that there is no difference in problem solving abilities between students who are taught the expository method with the inquiry method on the subject of similarity in mathematics subjects at MTs. NW Putra Narmada. This is evidenced by the results of data analysis obtained by the value of Zcount = 1.41, when compared with Ztable with a significant level of 5%, the value of Ztable = 1.96 is obtained. So that according to the test criteria if –Ztable = -1.96 Zcount = 1.41≤ Ztable = 1.96, then H0 is accepted.